Twin Town in South Brazil: a Nazi's experiment or a genetic founder effect? - Alice Tagliani-Ribeiro (Public Library of Science (PLoS), 2011)
Cândido Godói (CG) is a small municipality in South Brazil with approximately 6,000 inhabitants. It is known as the "Twins' Town" due to its high rate of twin births. Recently it was claimed that such high frequency of twinning would be connected to experiments performed by the German Nazi doctor Joseph Mengele. It is known, however, that this town was founded by a small number of families and therefore a genetic founder effect may represent an alternatively explanation for the high twinning prevalence in CG. In this study, we tested specific predictions of the "Nazi's experiment" and of the "founder effect" hypotheses. We surveyed a total of 6,262 baptism records from 1959-2008 in CG catholic churches, and identified 91 twin pairs and one triplet. Contrary to the "Nazi's experiment hypothesis", there is no spurt in twinning between the years (1964-1968) when Mengele allegedly was in CG (P = 0.482). Moreover, there is no temporal trend for a declining rate of twinning since the 1960s (P = 0.351), and no difference in twinning among CG districts considering two different periods: 1927-1958 and 1959-2008 (P = 0.638). On the other hand, the "founder effect hypothesis" is supported by an isonymy analysis that shows that women who gave birth to twins have a higher inbreeding coefficient when compared to women who never had twins (0.0148, 0.0081, respectively, P = 0.019). In summary, our results show no evidence for the "Nazi's experiment hypothesis" and strongly suggest that the "founder effect hypothesis" is a much more likely alternative for explaining the high prevalence of twinning in CG. If this hypothesis is correct, then this community represents a valuable population where genetic factors linked to twinning may be identified.